PERANCANGAN DAN IMPLEMENTASI CHATBOT BERBASIS NATURAL LANGUAGE PROCESSING UNTUK REKOMENDASI LAPTOP - Young, Filbert; Tukino (LPPM Universitas Putera Batam, 2025)
Technological advancements have significantly transformed the way people seek information, including in choosing electronic products such as laptops. However, consumers often face difficulties in making decisions due to the wide variety of laptops available, each with different specifications and price ranges. This study aims to design and implement a chatbot based on Natural Language Processing (NLP) that can automatically provide laptop recommendations according to users' needs. The chatbot is designed to understand users' queries in natural language and deliver relevant responses, such as laptop recommendations based on price ranges or specific needs like gaming, graphic design, or daily work. The development process utilizes NLP methods with machine learning algorithms to train the model to understand the context and intent of user inputs. The testing results show that the chatbot can provide recommendations that align with user requirements with a high level of accuracy. Moreover, the chatbot simplifies the process of obtaining information efficiently, thereby enhancing user experience in selecting electronic products. Future development may include expanding the laptop dataset, adding comparison features, and integrating with e-commerce platforms to deliver a more comprehensive solution.